Hajj, Its Islamic Perspective, Management and Role of Supply Chain in Indonesian Perspectives - Makrum Makrum (International Journal of Supply Chain Management, 2020)
Abstract- The aim of the existing literature is to investigate the hajj in the perspective of Islamic laws and also the impact of the importance of hajj on the hajj management system while taking supply chain management (SCM) as a mediator in the analysis. The data were gathered by using the survey questionnaires from the individual who going to perform hajj during hajj days by personal visit to the airports. PLS-SEM was used to analyze the collected data from the respondents. The results indicated that the hajj has greater importance in the eyes of Muslims with respect to Islamic laws and its effect positively on the hajj management system. The results also indicated that SCM practices also positively mediates among the importance of hajj as well as the hajj management system. These findings give the guideline to the hajj management teams that they should implement policies more carefully.